Epistemic Perspectives and Communicative Acts - Benz, Anton (Frontiers in Communication, 2021)
Searle (1969) introduced his famous distinction between constitutive and regulative rules that together define felicity conditions of speech acts. Regulative rules are normative rules, whereas constitutive rules define what counts as a performance of a speech act. In this paper we demonstrate with the example of assertions and referential uses of definite description that simple regulative rules can be given to speech acts that hold only on a core of well--behaved utterance situations. From this core, extended uses can be derived based on epistemic paths that are defined by the epistemic perspectives of speaker and hearer. As the use of speech acts get extended to a wider class of utterance situations, conflicts with the constitutive rules can emerge. We show that the extended uses are nevertheless felicitous. We represent epistemic relations in a possible worlds framework, and take an interactional approach that considers speech acts as part of joint communicative acts.